Flexible manufacturing system layout for furniture industry / Norlita Ibrahim, Norfajariah Mohamed Tarmidi and Norzakiya Norzain - Ibrahim, Norlita; Mohamed Tarmidi, Norfajariah; Norzain, Norzakiya (Faculty of Mechanical Engineering, 2002)
This thesis is written to understand flexible manufacturing system (FMS) and then to develop FMS layout for the furniture industry. We have chosen Tawei (M) Sdn Bhd as our case study company as they have given us the opportunity to further explores the potential to implement FMS in their plant. Our thesis starts with the understanding of FMS components. In general, FMS is defined as a fully automated operation yet flexible production for a family of parts. In studying FMS, the components consist of workstation, material handling, computer control system, and human resources. Besides that, types of layout is one of the characteristics involve in the designing of FMS layout. The FMS layout can be divided into five categories, such as in-line layout, loop layout, ladder layout, open-field layout, and robot centered layout. The technical definition of FMS is a production system consists of a set of identical or complementary numerically controlled machines that are connected through automated transportation systems. Each process in an FMS is controlled by a dedicated computer (FMS cell computer). This is often imbedded in a large hierarchical network of computers. An FMS is a capable of processing workpieces of a certain workpiece-spectrum in an arbitrary sequence with negligible setup delays between operations. This is possible since in an FMS a set of preadjusted tools is available through a centralized tool magazine with short access time or through local tool magazines at the machine with direct access. Furthermore workpieces are clamped on pallets at separate setup tables thus allowing them to be quickly positioned at the machines (T Horst and K Heinsrich, 1993)…